The Application Of Restirative Justice In The Crime Of Child Violence; Solutions Or Threats To The Sense Of Justice - Muhammad Hafiz Ingsaputro (Journal of Strafvordering Indonesian, 2025)
Cases of violence against children in Indonesia continue to increase, posing challenges for the justice system in balancing the punishment of perpetrators and the recovery of victims. The Restorative Justice (RJ) approach emerged as an alternative to case resolution that emphasizes victim recovery, perpetrator accountability, and community involvement. In the Indonesian legal system, RJ is accommodated through the Juvenile Criminal Justice System Law (SPPA Law) with a mechanism of diversion and penal mediation, which only applies to criminal acts with a threat of less than seven years and not the repetition of the crime. However, the application of RJ in cases of violence against children raises a dilemma, especially related to the risk of repeated trauma, social pressure, and potential injustice for victims. In addition, the effectiveness of RJ in providing a deterrent effect for perpetrators is still questionable. This study uses normative juridical methods with legislative and conceptual approaches to analyze related regulations and implications of RJ in child protection. The results of the study show that the implementation of RJ must be carried out with strict supervision, legal and psychological assistance for victims, and supervision mechanisms for perpetrators so as not to ignore the rights of victims. With clear regulations and strict supervision, RJ can be a more humane solution in handling cases of violence against children.